2004
DOI: 10.1095/biolreprod.103.026849
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Chaperone Proteins GRP78 and HSP60 on the Luminal Surface of Bovine Oviduct Epithelial Cells and Their Association with Spermatozoa1

Abstract: Upon their transit through the female genital tract, bovine spermatozoa bind to oviduct epithelial cells, where they are maintained alive for long periods of time until fertilization. Although carbohydrate components of the oviduct epithelial cell membrane are involved in these sperm/oviduct interactions, no protein candidate has been identified to play this role. To identify the oviduct factors involved in their survival, sperm cells were preincubated for 30 min with apical membranes isolated from oviduct epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
74
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 52 publications
10
74
1
1
Order By: Relevance
“…Like the study reported here, experiments by Boilard and colleagues (Boilard et al 2001) identified three chaperone proteins from cow oviducts that bound to bull spermatozoa; two of these were identified as Heat shock 60 kDa protein 1 (chaperonin; HSPD1 previously known as HSP60) and HSPA5 (Boilard et al 2004). Interestingly, HSPA5 is also present in our sperm-binding 70 kDa sAPM band.…”
Section: Hspa8 and Boar Spermsupporting
confidence: 77%
See 1 more Smart Citation
“…Like the study reported here, experiments by Boilard and colleagues (Boilard et al 2001) identified three chaperone proteins from cow oviducts that bound to bull spermatozoa; two of these were identified as Heat shock 60 kDa protein 1 (chaperonin; HSPD1 previously known as HSP60) and HSPA5 (Boilard et al 2004). Interestingly, HSPA5 is also present in our sperm-binding 70 kDa sAPM band.…”
Section: Hspa8 and Boar Spermsupporting
confidence: 77%
“…They are known to be synthesized during spermatogenesis (Allen et al 1988, Maekawa et al 1989 and they adopt specific localizations within sperm e.g. within their plasma membrane (Boilard et al 2004, Mitchell et al 2007. While endogenous heat shock proteins clearly have roles in sperm function, data in the present study clearly show that exogenous heat shock proteins, such as HSPA8 can also have an important effect on sperm function.…”
Section: Hspa8 and Boar Spermmentioning
confidence: 42%
“…HSPA8 probably reverses sperm membrane damage and restores cell membrane integrity via interactions with, and alterations in, membrane properties. A number of studies have reported on the ability of different HSPs to enhance viability via interactions with cellular membranes in different cell types (Johnson et al 1990, Johnson & Tytell 1993, Boilard et al 2004. It is known that HSPs regulate membrane stability and fluidity (Chen et al 2005, Horvath et al 2008 and that HSPs are involved in stabilizing cellular and organellar membranes in stressful conditions (Carratu et al 1996, Vigh et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis of porcine oviductal fluid has revealed that epithelial cells in the oviductal lumen secrete several molecules in response to the presence of spermatozoa, most notable of which are heat shock (stress) proteins (HSPs) (116). Heat shock proteins have also been identified in soluble fractions of pig and cow oviductal apical plasma membranes (sAPM) and in the human apical epithelium (117)(118)(119). These are potentially important findings, as the oviduct and oviductal sperm storage play key roles in reproduction by providing a secure reservoir in which spermatozoa can attain full fertilising properties.…”
Section: Extracellular Cell Stress Proteins In Cancermentioning
confidence: 99%